Upregulation of angiogenesis in oral lichen planus. (12th December 2017) - Al‐Hassiny, A.; Friedlander, L. T.; Parachuru, V. P. B.; Seo, B.; Hussaini, H. M.; Rich, A. M.
Abstract : Objectives: As angiogenesis is fundamental to the pathogenesis of many chronic inflammatory disorders, this study investigated the expression of various vascular markers in oral lichen planus and non‐specific oral mucosal inflammatory tissues. Methods: Archival specimens of oral lichen planus (n = 15) and inflamed tissues (n = 13) were stained using immunohistochemistry with antibodies to CD34, vascular endothelial growth factor, vascular endothelial growth factor receptor and vasohibin. Nine representative sites at the epithelial‐connective tissue junction and through the fibrous connective tissue were selected, and automated analysis techniques were used to determine the extent of positivity expressed as the percentage of positive cells. Significance was denoted when P  < .05. Results: The expression of pro‐angiogenic factors was higher in lichen planus samples compared with inflamed controls. A higher level of CD34 was observed in the deeper parts of the connective tissue of Oral lichen planus (OLP) ( P  = .04), whereas VEGF and VEGFR2 expressions were higher all through the tissues (respectively, P  < .02 and P  < .01). The expression of the anti‐angiogenic VASH1 was higher in inflamed tissue compared with lichen planus in all sites evaluated ( P  < .01). Conclusions: The findings indicate that angiogenic factors are differentially expressed in oral lichen planus compared with inflamed controls, with increased expression of pro‐angiogenic factors and decreased anti‐angiogenic expression.